AN INFLUENCE OF SERVICE QUALITY AND CAFE ATMOSPHERE ON CUSTOMER INTEREST TO RETURN VISIT STARBUCK IN MEDAN CITY - Indawati Lestari (SEAN Institute, 2023)
This study aims to determine the effect of service quality and cafe atmosphere on the intention to revisit Starbucks customers in Medan City. The population in this study were customers who visited Starbucks in (June 2021-May 2022), namely 5,778. The selection of the sample in this study was based on the calculations put forward by Slovin so that the sample obtained was 99 respondents. The data analysis technique used is multiple linear regression test. The results showed that service and cafe atmosphere had a positive and significant effect on the intention to revisit Starbucks customers in Medan City.